Difusi Inovasi dalam Konteks Pemberdayaan Masyarakat - shinta prastyanti (Jurnal Ilmu Komunikasi Acta Diurna, 2013)
Diffusion of innovation consists of several components, one of which is the message or the innovation itself. There is a view that an innovation is often concluded with the adoption of an innovation by the community, when in fact it is not always the case. In line with this opinion as if the diffusion of innovations is only focus on the spreading of innovation to the community and innovation is seen as an idea, an idea, a method, a new product in development communication perspective. On the other hand as far as this empowerment is reviewing how to make a community can utilize its resources as much as possible so the people become empowered, eventhough in the process of empowerment is not solely rely on the ability of local only and ignore the role of the outsider. Outsider's contribution in the process of community empowerment is as a facilitator who assist the people to identify and to manage the social capital possessed to gain wider access in order to improve their quality of life. In this case, an innovation can be one of the important aspects of community empowerment